Research Action Plan for AGROSAVIA Carmen de Bolivar: Participative analysis aimed to improve RDI capacity - Arias-Robles, Milena; Burbano-Figueroa, Oscar; Londoño Salcedo, Wilman (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Action plans are instruments aimed at supporting the implementation and execution of research agendas in social enterprises providing timelines and mechanisms for stakeholder participation. This paper describes the action plan 2018-2028 for the Carmen de Bolivar Research Station (CB-RS), a member of the AGROSAVIA Corporation in Colombia. This plan is oriented to promote the competitiveness and sustainability of this RS and increase the impact on its hinterland: the states of Sucre and Bolivar. We build this plan as a participatory process of three methodological steps: assessment of the CB-RS´s current situation, identification of competitive advantages, and design of the action plan. The current situation assessment showed a local research gap related to the need for harvest and postharvest technologies and the redundant unnecessary provision of new plant cultivars and breeding programs. Using this gap, we promote the participative creation of a portfolio of strategic actions that includes the creation of technological innovations suited to the needs of local stakeholders. The findings described here are an important input for creating a new CBRS plan of action in the post-pandemic scenario.